2023
DOI: 10.1364/oe.472070
|View full text |Cite
|
Sign up to set email alerts
|

Polarization calibration assessment for a broadband imaging polarimeter based on a division of aperture architecture

Abstract: This article intends to provide all the experimental insights and analyze the best polarimetric calibration method for a division of aperture polarimetric imager considering the different implications it has on the experimental set-up and its performance. Polarimetric cameras require careful calibration for the correct measurement of polarization information. The calibration methods are introduced, intermediate results are presented, and the ability of the set-up to estimate Stokes vectors and Mueller matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Several methods exist in the literature and some of them are specially designed for the polarimeter under development. A comparison 12 was performed regarding the general methods, to find the most suitable method for a DoAP imaging polarimeter. The results concluded that the Data Reduction Matrix method 13,14 (DRM) performs better for a full-Stokes polarimeter working in the VIS range.…”
Section: Calibration Of the Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Several methods exist in the literature and some of them are specially designed for the polarimeter under development. A comparison 12 was performed regarding the general methods, to find the most suitable method for a DoAP imaging polarimeter. The results concluded that the Data Reduction Matrix method 13,14 (DRM) performs better for a full-Stokes polarimeter working in the VIS range.…”
Section: Calibration Of the Systemmentioning
confidence: 99%
“…A solution to this issue 13 is to use SVD to recover the pseudoinverse of 𝑰𝑰. The procedure and the experimental set-up for the polarimetric calibration are explained in Peña-Gutiérrez et al 12 , where optimal RPS are employed to reduce the error in acquisition.…”
Section: Calibration Of the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This analyser is comprised of elliptical four polarization states, one for each optical path resulting from the division at the aperture. Each of these RPS is generated by a retarder and a horizontal linear polarizer [9][10] , which is common for all the retarders.…”
Section: Polarimetric Cameramentioning
confidence: 99%
“…The radiometric calibration accounts for the variance of the behaviour of the pixels in the sensor. Therefore, we characterise the sensor by measuring the dark noise response when no excitation of the pixels is present and the flat pattern which shows the behaviour of each pixel when the surface is homogeneously illuminated 10 . This pattern can retrieve the differences between pixels at the centre or on the sides and get rid of dead and saturated pixels.…”
Section: Radiometric and Geometric Calibrationmentioning
confidence: 99%